Does society need an intellectual property right for press publishers? - Díaz-Noci, Javier (Anuario ThinkEPI, 2017)
The European Commission published, in September 2016, a proposal for a new directive regarding copyright and digital society, which included a new right that addressed the needs of press publishers. This directive can be interpreted as a promise to effectively enact such a right. This move was the result of lobbying pressure by newspaper publishers´ groups and companies, whose aims were to provide a partial solution to the decreasing revenues in advertisement caused by the general economic crisis and the Internet. The initiative is the result of previous lobbying activities, which were effective in reforming the copyright acts of both Germany and Spain in 2014-2015, but ineffective in making anyone pay press publishers. In this article we analyze the pros and cons of the newly announced press publishers´ right and the form it could take if finally, attending to the pressure of press groups and against the opinion of the whole of academia and of many of the other involved actors, the European institutions decide to go ahead and enact this right.
Keywords: Intellectual property; Copyright; Press publishers´ right; Ancillary rights; European Union